Quantitative assessment of the oxidation potential of sulfide-bearing aggregates in concrete using an oxygen consumption test. (March 2016) - Rodrigues, Andreia; Duchesne, Josée; Fournier, Benoît
Abstract: In the presence of oxygen and humidity, the iron sulfide minerals present in some concrete aggregates can oxidize creating damage to concrete infrastructure. An oxygen consumption test was developed to assess the oxidation potential of concrete aggregate. A compacted layer of aggregate material is exposed to oxygen (O2 ) in a hermetic cell, and the O2 consumption is monitored. Optimized parameters included a 10 cm compacted layer of aggregate material with particle size <150 μm kept at 40% saturation degree with a 10-cm headspace left at the top of the cell. The consumption of the O2 present in the headspace is monitored over a 3-h testing period at 22 °C. The test was able to discriminate the eight sulfide-bearing and control aggregates selected when using a threshold limit of 5% O2 consumed. This draft limit will, however, require to be confirmed through the testing of a larger number of aggregates.